HOW THE PARATEXT SURVIVED THE MASTERPIECE - Guliashvili, Sophia (PEOPLE: International Journal of Social Sciences, 2024)
There are 164 survived manuscripts of the masterpiece of the Georgian and world literary heritage The Man in the Panther Skin by Shota Rustaveli (12th century), rewritten in the 17th century and after. The oldest record belongs to the edge of the 16th-17th centuries and the oldest manuscript dates back to 1646. Before the appearance of the 1st printed version, that is, until 1712, the epic reached in one editorial version, which is clearly not from Rustveli’s hands. All manuscripts containing this edition are preceded by the pseudo-Rustavelian introductory stanza that presents the poem as a secular work differing from the church ideology and writings; which teaches and advises the reader to distance themselves from the secular ideology of Persian origin represented in the epic, and says that monks and nuns are forbidden to pay attention to this ideology, so they mustn't read this text. It is interesting, that only those manuscripts of the epic have survived, which represented this one and only redaction where the text was preceded by a pseudo-Rustavelian stanza. The detailed information on the manuscripts of The Man in the Panther Skin and the reality which made the pseudo-Rustavelian stanza to be useful in survival of “The Man in the Panther Skin” will be discussed in the current paper